Geostrategi dalam dinamika global: Implikasi bagi ketahanan nasional - Hakim, Erwin Maulana (Maliki Interdisciplinary Journal, 2025)
Geostrategy in an increasingly complex global context, is not only related to military aspects but also encompasses various dimensions such as economy, politics, technology, and diplomacy. Through the analysis of various approaches and policies of major countries such as the United States, China, and Russia, it is evident how economic and technological power is utilized as a geostrategic tool to maintain and expand influence. In addition, this study emphasizes the importance of Indonesia’s adaptation to global geopolitical changes through a comprehensive strategy, including the strengthening of national resilience in sectors such as education, society, and the economy. A comprehensive understanding of geostrategy will assist Indonesia in formulating proactive foreign policies and strengthening its strategic position in the Indo-Pacific region and the international arena in general.